Augmentation in Tribological Performance of Polyalphaolefins by COOH-Functionalized Multiwalled Carbon Nanotubes as an Additive in Boundary Lubrication Conditions - Kumar H.; Harsha A.P. (My University, 2025)
This current study emphasized the tribological performances of COOH-functionalized multiwalled carbon nanotubes (MWCNTs) dispersed in two different grades of polyalphaolefins (i.e., PAO 4 and PAO 6). The friction and wear properties have been estimated using SRV 5 tribometer with “ball-on-disc” configuration. Prior to tribo testing, MWCNTs were characterized by X-ray diffractometer (XRD), high-resolution transmission electron microscopy (HR-TEM), and Fourier-transform infrared spectroscopy (FTIR). The varying dose of MWCNTs (0.025-0.15 wt%) was incorporated into both PAO base oils to obtain the optimized lubrication behavior. The test results revealed that PAO 4 exhibited a reduction in friction coefficient (∼27%) and wear volume (∼88%) at a dose of 0.05 wt% and 0.025 wt % MWCNTs, respectively. However, in PAO 6, the minimum coefficient of friction and wear volume was obtained at a concentration of 0.075 wt% and 0.05 wt% of the additive. The results evidenced that PAO 6 based nanolubricants demonstrated the best frictional characteristics while attained the best anti-wear performance with PAO 4 based nanolubricants. For the better unveiling of the lubrication mechanism of MWCNTs, worn surfaces were characterized using various analytical techniques such as scanning electron microscopy (SEM), scanning probe microscope (SPM), energy-dispersive X-ray spectroscopy (EDS), and X-ray photoelectron microscopy (XPS). Copyright © 2021 by ASME